Surface-dopylated carbon nanoparticles sense gas-induced ph changes - Ibrahim, Norahim (Elsevier B. V, 2012)
Carbon nanoparticles of ca. 9-18 nm diameter (Emperor 2000™) are surface-modified by covalently linking l-dopa-boc (boc-protected l-3,4-dihydroxyphenylalanine) with a surface coverage of approximately 100 per particle (or 3 × 10 13 cm -2). In solution environments these redox-active nanoparticles provide chemically stable and pH-sensitive voltammetirc responses (reversible 2-electron 2-proton oxidation) over a pH range from 2 to 12. When mixed into Dowex 50 Wx4 cation exchanger or Dowex 50 1x2 anion exchanger and placed in contact with a glassy carbon electrode in a flow of humidified gas, the l-dopa-boc-modified carbon nanoparticles provide pH-sensitive surface probes to monitor the surface conditions. In a two-terminal cell it is demonstrated that gas flow measurements are possible with both modified cation and anion exchanger particles in contact to glassy carbon electrodes. The anion exchanger particles allow pH control after pre-conditioning in phosphate buffer. Loading-dependent sensitivity to ammonia gas is investigated and high sensitivity to ammonia is observed for Dowex 50 1x2 anion exchanger pre-equilibrated in phosphate buffer pH 3 and decorated with l-dopa-boc-modified carbon nanoparticles. Responses are observed with sequential injections of 1 cm 3 ammmonia into a gas flow-through device.